THE INTRACELLULAR LOCALIZATION OF INORGANIC CATIONS WITH POTASSIUM PYROANTIMONATE : Electron Microscope and Microprobe Analysis - Tandler, Carlos J. (The Rockefeller University Press, 1970)
Potassium pyroantimonate, when used as fixative (saturated or half-saturated, without addition of any conventional fixative) has been demonstrated to produce intracellular precipitates of the insoluble salts of calcium, magnesium, and sodium and to preserve the general cell morphology. In both animal and plant tissues, the electron-opaque antimonate precipitates were found deposited in the nucleus—as well as within the nucleolus—and in the cytoplasm, largely at the site of the ribonucleoprotein particles; the condensed chromatin appeared relatively free of precipitates. The inorganic cations are probably in a loosely bound state since they are not retained by conventional fixatives. The implications of this inorganic cation distribution in the intact cell are discussed in connection with their anionic counterparts, i.e., complexing of cations by fixed anionic charges and the coexistence of a large pool of inorganic orthophosphate anions in the nucleus and nucleolus.